[Rural Village, Trinidad, B.W.I.] - (:unkn) unknown (My University, 2009)
A picture of a small rural village with wooden structures lining the unpaved dirt road. An automobile is parked at the far end of the road. The postcard is addressed to Mr. Paul Urich, Mayaro. Affixed to the postcard is a Trinidad and Tobago 1 half penny stamp.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Villages--Trinidad and Tobago; [1900]; Buildings--Trinidad and Tobago; General stores--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Beaches--Trinidad and Tobago; Architecture--Trinidad and Tobago; Country life--Trinidad and Tobago